Evaluation Of Activated Carbon Generated From Waste As A Low-Cost Adsorbent For The Removal Of Surfactants From Wastewater - Nor Hidayu, Binti Mohd Samsudin (Universiti Malaysia Sarawak (UNIMAS), 2011)
Hen eggshell is the one of the major by product of the food industry. Due to its large production, the use of hen eggshell as low-cost activated carbon has slightly increased in recent years. Thus in this study, eggshell and its membrane particle was evaluate from the hen eggshell to be prepared as an activated carbon as a low cost adsorbent for the removal of surfactant, anionic, sodium dodecyl sulfate (SDS). In this work, a kinetic study was done with respect to different adsorbent dose against contact time in the adsorption process. The removal of surfactant was measure using UV Visible Spectrophotometer. The morphology was observed by SEM imaging. The Fourier transform infra-red (FTIR) spectra proved the presence of functional groups such as hydroxyl, amine and carbonyl groups.